Fractional Order PID Control Strategy of SWISS Rectifier - WANG Jitao; LIU Mingliang; XU Senyang; WANG Xizhe; ZHU Qiang (Journal of Harbin University of Science and Technology)
In response to the problems of slow dynamic response speed and poor robustness of the traditional integer order PID control strategy for SWISS rectifiers, this paper proposes a control strategy for SWISS rectifiers based on fractional order PID. Based on the working principle of SWISS rectifier, its Small-signal model is established, the equivalent transfer function of SWISS rectifier is obtained, and a double closed loop control structure based on fractional PID voltage control is designed. To simplify the order parameter design of fractional order PID, the integer order PID parameter pre-tuning method is used to obtain the initial parameter values, and particle swarm optimization algorithm is used to further design and optimize the fractional order PID controller parameters. The simulation and experimental results show that under the fractional order PID control strategy, the voltage stability time of the SWISS rectifier is less than 7ms when the reference voltage suddenly changes, and the overshoot is less than 2% . When the load disturbance occurs, the voltage stability time is less than 4ms, and the overshoot is less than 3% . The dynamic performance is better than the integer order PID control strategy.